A 3D printed polylactic acid-Baghdadite nanocomposite scaffold coated with microporous chitosan-VEGF for bone regeneration applications. (15th July 2023) - Salehi, Saeideh; Tavakoli, Mohamadreza; Mirhaj, Marjan; Varshosaz, Jaleh; Labbaf, Sheyda; Karbasi, Saeed; Jafarpour, Farnoosh; Kazemi, Nafise; Salehi, Sepideh; Mehrjoo, Morteza; Emami, Eshagh
Abstract: Three-dimensional (3D) printing technology has become an advanced approach for fabricating patient-specific scaffolds with complex geometric shapes to replace damaged or diseased tissue. Herein, polylactic acid (PLA)-Baghdadite (Bgh) scaffold were made through the fused deposition modeling (FDM) 3D printing method and subjected to alkaline treatment. Following fabrication, the scaffolds were coated with either chitosan (Cs)-vascular endothelial growth factor (VEGF) or lyophilized Cs-VEGF known as PLA-Bgh/Cs-VEGF and PLA-Bgh/L.(Cs-VEGF), respectively. Based on the results, it was found that the coated scaffolds had higher porosity, compressive strength and elastic modulus than PLA and PLA-Bgh samples. Also, the osteogenic differentiation potential of scaffolds following culture with rat bone marrow-derived mesenchymal stem cells (rMSCs) was evaluated through crystal violet and Alizarin-red staining, alkaline phosphatase (ALP) activity and calcium content assays, osteocalcin measurements, and gene expression analysis. The release of VEGF from the coated scaffolds was assessed and also the angiogenic potential of scaffolds was evaluated. The sum of results presented in the current study strongly suggests that the PLA-Bgh/L.(Cs-VEGF) scaffold can be a proper candidate for bone healing applications. Graphical abstract: Unlabelled Image